Human tissue research a European perspective on the ethical and legal challenges - Lenk, Christian (Oxford : Oxford University Press, 2011)
The use of human tissue for medical research and scientific progress raises many ethical and legal challenges. This text provides a fascinating insight into interlinking research perspectives and serves as a comprehensive reference to the state of play ethically and legally in Europe.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Tissue engineering; Tissue engineering -- Moral and ethical aspects; Tissue engineering -- Law and legislation -- Europe